Changes in hospital bond ratings after the transition to a new electronic health record. (20th February 2018) - McEvoy, Dustin; Barnett, Michael L; Sittig, Dean F; Aaron, Skye; Mehrotra, Ateev; Wright, Adam
Abstract: Objective: To assess the impact of electronic health record (EHR) implementation on hospital finances. Materials and Methods: We analyzed the impact of EHR implementation on bond ratings and net income from service to patients (NISP) at 32 hospitals that recently implemented a new EHR and a set of controls. Results: After implementing an EHR, 7 hospitals had a bond downgrade, 7 had a bond upgrade, and 18 had no changes. There was no difference in the likelihood of bond rating changes or in changes to NISP following EHR go-live when compared to control hospitals. Discussion: Most hospitals in our analysis saw no change in bond ratings following EHR go-live, with no significant differences observed between EHR implementation and control hospitals. There was also no apparent difference in NISP. Conclusions: Implementation of an EHR did not appear to have an impact on bond ratings at the hospitals in our analysis.